Monitoring Surface Deformation Of Coal Mining Waste Dumps With Time Series Insar Analysis - Wardhana, Gunawan Wisnu; Hayati , Noorlaila (Syntax Corporation, 2025)
Surface deformation is a common phenomenon in coal mining operation especially waste dump areas. Overburden dumping activities creates slopes that are potentially susceptible to landslides. It is crucial to consider the factors affecting slope stability during the planning, execution, and post-formation stages of waste dump areas. One of the methods for controlling landslide risk involves the installation of in-situ sensors to monitor the stability of waste dump areas using GPS Monitoring sensors. However, there are challenges associated with limited monitoring coverage, equipment costs, and security risks of the equipment in conducting comprehensive in-situ stability monitoring of the entire waste dump areas. An alternative method is proposed for identifying the deformation in waste dump areas using Interferometric Synthetic Aperture Radar (InSAR) method with Sentinel-1 imagery data. This study present time-series InSAR analysis for monitoring surface deformation of coal mining waste dumps using MintPy software and Hyp3 ASF DAAC on-demand InSAR data. The results show that the displacement derived from InSAR analysis agree well with the displacement measured by GPS with RMSE value is 0.035 meter and R2 is 0.83. However, some discrepancies were found at the HW12 waste dump area, where InSAR could not detect the very high displacement captured by the GPS monitoring station. On the other hand, InSAR analysis reveals a more detailed spatial distribution of surface deformation compared to the GPS monitoring station, providing valuable insight to mitigate risks and ensure the safety and stability of mining operations, particularly in waste dump areas.